FIVE-YEAR EXPERIENCE OF HIGHLY ACTIVITY ANTIRETROVIRAL THERAPY IN CHILDREN WITH HIV-INFECTION - V. B. Denisenko; E. N. Simovanyan (Детские инфекции (Москва))
Clinical, immunological and virologic examination of 67 HIV infected children receiving highly activity antiretroviral therapy (HAART) within 12—60 months is conducted. HAART promoted suppression of HIV replication, increase of T-helpers count, reduction of clinical symptoms frequency and its expressiveness. At long HAART application the considerable part of patients needs therapy correction because of loss of efficiency of the starting scheme or development of side effects. For increase of therapy efficiency it is necessary lopinavir/ritonavir to include in HAART schemes, and also to carry out selection of preparations taking into account HIV drug resistance.